How does taking a political or social stance influence the way consumers form associations and expectations of a brand? - Casey,Lauren; Bjerström,Ellen; Bekes,Max Johan (LBMG Strategic Brand Management - Masters Paper Series, 2025)
Purpose: This paper aims to uncover the associations and expectations consumers develop from a brand taking a political or social stance. We build upon existing literature to offer managers, and the research field, valuable insights to bridge the knowledge gap on what to consider before taking a stance. This paper guides the reader through a set of key considerations to evaluate before taking actions that could harm an organization’s brand image. Research question: How does taking a political or social stance influence the way consumers form associations and expectations of a brand? Methodology: In this paper we build on existing literature using a qualitative approach with the data collection of three focus groups. Each group was composed of six to eight political science and marketing students. The groups were presented with cases of Ben & Jerry’s and Nike with their political marketing campaigns, taking clear stances in political and social matters. Findings: Our findings highlight the importance of authenticity in politically or socially loaded messages from brands, as well as how they align with their image and identity. Additionally, brand associations have been proven to be more challenging as consumers expect more from brands in this generation. Therefore, we came up with a set of five “W-questions” that can be used as a guide before taking a stance in political and social matters. Original/value: The paper provides value by extending the existing literature and guides managers and research within political marketing. Our study contributes findings on how politically charged advertising affects consumers' associations and expectations. This bridges the gap in the literature rather than filling the gap completely.
Keywords: Political Marketing; Brand Identity; Brand Image; Brand Associations